Persepsi Siswa terhadap Penggunaan Metode Role Playing dalam Pembelajaran Pendidikan Agama Buddha: Students' Perceptions of the Use of the Role-Playing Method in Buddhist Religious Education - Visaka Damayanti; Sutikyanto Sutikyanto; Maria Fransisca Andanti (ITScience (Information Technology and Science), 2026)
Active learning methods, such as role-playing, serve as relevant strategies for creating meaningful learning experiences, particularly in Buddhist Religious Education, a subject rich in Dhamma values ??like *mett?* (loving-kindness), *karu??* (compassion), and *s?la* (virtuous conduct). This study aims to describe and gain an in-depth understanding of 8th-grade students' perceptions regarding the use of role-playing in Buddhist Religious Education, examining the cognitive, affective, and conative dimensions. A qualitative descriptive approach was employed, with three students serving as key informants selected through purposive sampling. Data were collected via observation, in-depth interviews, and documentation, then analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which encompasses data reduction, data display, and conclusion drawing/verification. The findings indicate that role-playing helps students internalize storylines and moral messages—especially when dealing with narrative material featuring specific characters—although abstract concepts still require additional explanation from the teacher. Emotionally, students experienced nervousness and anxiety before performing, which shifted to relief and happiness upon completion, with the intensity varying according to each individual's level of preparedness. Furthermore, role-playing fostered courage and self-confidence over time while cultivating teamwork and a sense of responsibility within student groups. Thus, student perceptions of role-playing are multidimensional and personal, shaped by the interaction between the teacher's instructional design and the students' individual characteristics; consequently, teachers must remain sensitive to the nature of the material and the students' psychological readiness when implementing this method.